Analisis Tingkat Kepatuhan terhadap Standar Operasional Prosedur (SOP) dalam Program Pelatihan DPK BRIN - Anwar, Rinawati; Shofa, Hilyatush; Lestari, Restu; Sediadi, R.M. Agus (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Standard Operating Procedures (SOPs) play a crucial role in ensuring the effectiveness and efficiency of training implementation, particularly in organizations managing human resource development. This study aims to evaluate the level of compliance with SOPs in training programs organized by the Directorate of Competency Development (DPK) at the National Research and Innovation Agency (BRIN). The evaluation was conducted on 36 training programs across four categories: National HR, Nuclear Technology, Licensing, and International HR. A quantitative approach was employed, utilizing descriptive statistics and a Single Factor ANOVA test to determine differences in compliance levels among training categories. The results indicate that the majority of training programs were conducted in accordance with SOPs, with a compliance rate of 66.7%. The National HR and Nuclear Technology categories exhibited the highest compliance levels (27.8% each), whereas the Licensing training category had the lowest compliance rate, with 19.4% deemed non-compliant. Statistical analysis revealed significant differences in SOP compliance among the training categories, highlighting the need for improvement strategies, particularly in newly introduced or underperforming training categories. These findings emphasize that adherence to SOPs contributes to the effectiveness of training implementation and the quality of competency development programs. Therefore, efforts should be made to enhance SOP understanding, provide training for administrators, and strengthen monitoring and evaluation systems to ensure higher quality standards in training implementation